2016
DOI: 10.1108/sc-10-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Youth in the UK: 99 problems but the gang ain ' t one?

Abstract: Youth in the UK: 99 problems but the gang ain ' t one?Hannah Smithson Rob Ralphs Article information:To cite this document: Hannah Smithson Rob Ralphs , (2016),"Youth in the UK: 99 problems but the gang ain ' t one?", Safer Communities, Vol. 15 Iss 1 pp. 11 -23 Permanent link to this document: http://dx.(2016),"Towards an intersectional model of desistance for black offenders", Safer Communities, Vol. 15 Iss 1 pp. 24-32 http:// dx.(2016),"Managing offenders: establishing the impact of incarceration and what wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Pitts, he concluded, had succumbed to unguarded 'gang talk' (Hallsworth and Young 2008) and was reminded that loose lips sink ships. Hallsworth foreshadowed heavy criticism of subsequent government policy on gangs (see Shute and Medina 2014;Smithson and Ralphs 2016), with some commentators arguing the 'G-word' helped politicians justify the scapegoating and criminalization of black and minority ethnic youth (Alexander 2008;Gunter 2017;Smithson et al 2012;Williams 2015). Pitts (2012Pitts ( , 2016 responded in kind to these criticisms, describing the academics underplaying victim impact or neutralizing harm caused by gangs as 'reluctant criminologists' blinded by cognitive dissonance and in dereliction of their professional duty to transform private troubles into public issues.…”
Section: Literature Review: a Decade Of Uk Gang Researchmentioning
confidence: 99%
“…Pitts, he concluded, had succumbed to unguarded 'gang talk' (Hallsworth and Young 2008) and was reminded that loose lips sink ships. Hallsworth foreshadowed heavy criticism of subsequent government policy on gangs (see Shute and Medina 2014;Smithson and Ralphs 2016), with some commentators arguing the 'G-word' helped politicians justify the scapegoating and criminalization of black and minority ethnic youth (Alexander 2008;Gunter 2017;Smithson et al 2012;Williams 2015). Pitts (2012Pitts ( , 2016 responded in kind to these criticisms, describing the academics underplaying victim impact or neutralizing harm caused by gangs as 'reluctant criminologists' blinded by cognitive dissonance and in dereliction of their professional duty to transform private troubles into public issues.…”
Section: Literature Review: a Decade Of Uk Gang Researchmentioning
confidence: 99%
“…As research has demonstrated, moreover, there are wide variations in the meaning and application of the term ‘gang’ both within jurisdictions such as the UK (Fraser, ), between the USA and UK (Fraser and Hagedorn, ; Hallsworth and Brotherton, ), and among criminal justice practitioners across these differing jurisdictions. The picture is still emerging and clearly lacking several pieces of the jigsaw (Ralphs and Smithson, ; Smithson and Ralphs, ).…”
Section: Gangs Punitivism and Policy Mobilitymentioning
confidence: 99%
“…This is a thorny subject, particularly in the UK. Some researchers have argued that youth gang ‘problems’ are hyped up by professionals and ‘gang talkers’ with vested interests in exaggerating the nature and scale of youth gangs (Hallsworth & Young, ; Smithson & Ralphs, ). Others, however, have highlighted the serious levels of violence committed by people involved in street gangs and the negative effects that gang involvement has on outcomes for young people (Pitts, ; Densley, ; Harding, ).…”
Section: A Note On Terminologymentioning
confidence: 99%
“…An established body of research indicates that gang‐involved young people have an increased propensity to become both offenders and victims of crime, experience breakdowns in their familial and personal relationships, and engage in illicit substance use (Thornberry et al ., ; Krohn et al ., ; Melde & Esbensen, ; Ozer & Engel, ; Weerman et al ., ). The issue of youth gangs was pushed up the UK political agenda by the 2011 riots and the contentious debates that followed regarding the role played by school‐aged young people involved in gangs (Ministry of Justice, ; Home Office, ; Smithson & Ralphs, ). Recent police data indicate that the problems associated with youth gangs have been growing since the riots, with the number of gang‐related violent offences increasing by 55% between 2013 and 2015, and over one in five knife crimes with serious injury in 2015 being gang‐related (MOPAC, ).…”
Section: Introductionmentioning
confidence: 99%